The energetics of semicontact 3 x 2-min amateur boxing - Davis, P.; Leithäuser, R. M.; Beneke, R. (International Journal of Sports Physiology and Performance, 2014)
The energy expenditure of amateur boxing is unknown. Purpose: Total metabolic cost (Wtot) as an aggregate of aerobic (Waer), anaerobic lactic (W[lactate]), and anaerobic alactic (WPCr) energy of a 3 × 2-min semicontact amateur boxing bout was analyzed. Methods: Ten boxers (mean ± SD [lower/upper 95% confidence intervals]) age 23.7 ± 4.1 (20.8/26.6) y, height 180.2 ± 7.0 (175.2/185.2) cm, body mass 70.6 ± 5.7 (66.5/74.7) kg performed a semicontact bout against handheld pads created from previously analyzed video footage of competitive bouts. Net metabolic energy was calculated using respiratory gases and blood [lactate]. Results: Waer, 526.0 ± 57.1 (485.1/566.9) kJ, was higher (P < .001) than WPCr, 58.1 ± 13.6 (48.4/67.8) kJ. W[lactate], 26.2 ± 7.1 (21.1/31.3) kJ, was lower (P < .001) than Waer and WPCr. An ~70-kJ fraction of the aerobic energy expenditure reflects rephosphorylation of high-energy phosphates during the breaks between rounds, which elevated Wtot to ~680 kJ with relative contributions of 77% Waer, 19% WPCr, and 4% W[lactate]. Conclusions: The results indicate that the metabolic profile of amateur boxing is predominantly aerobic. They also highlight the importance of a highly developed aerobic capacity as a prerequisite of a high activity rate during rounds and recovery of the high-energy phosphate system during breaks as interrelated requirements of successful boxing.